Sugarcane Bagasse: A Potential Medium for Fungal Cultures. (13th March 2014) - Sidana, Arushdeep; Farooq, Umar
Abstract : Worldwide, sugarcane industries produce tons of sugarcane bagasse as residual/waste material. This residual material is rich in complex lignocellulosic substances and may be used as a low cost carbon and energy source for the growth of fungal species. The present work was aimed at designing a sugarcane waste-based medium as a substitute for expensive commercial media for growing fungal cultures. Eight species of fungi, namely, Aspergillus niger, Candida albicans, Saccharomyces cerevisiae, Fusarium sp., and four unidentified species F1, F2, F3, and F5, were grown on the sugarcane bagasse medium which produced remarkable results and competed with standard media like potato dextrose agar, Sabouraud dextrose agar, and cornmeal agar. The designed medium was able to provide nourishment to the fungi as well as prevent the growth of any bacterial or fungal contaminant. The production of spores was more in the sugarcane medium as compared with standard media. Hence, this study led to the discovery of a new and efficient medium for fungal cultures as well as decrease in the waste disposal expenses and efforts.